Jatropha developments in Mozambique: analysis of structural conditions influencing Nicheregime interactions - Slingerland, Maja; Schut, Marc (MDPI, 2014)
This article investigates the transition dynamics related to Jatropha developments in Mozambique. The analysis focuses on how structural conditions (infrastructure, institutions, interaction and collaboration and capabilities and resources) enable or constrain interactions between niche-level Jatropha experiments and incumbent energy, agriculture and rural development regimes in Mozambique. Investors in agro-industrial Jatropha projects focused on establishing projects in areas with relatively good infrastructure, rather than in remote rural areas. Furthermore, they predominantly focused on Jatropha production instead of investing in the entire Jatropha value chain, which turned out to be a challenge in itself, as growing a productive Jatropha crop was much more complex than initially anticipated. The development of institutions that could nurture and protect Jatropha projects from the prevailing regimes lagged behind Jatropha project establishment, leading to an insecure investment climate. Strong inter-ministerial collaboration and organized civil society interaction and representation contrasted with non-organized private sector and rather isolated smallholder Jatropha projects. The global financial crisis and limited adaptive capacity reduced the time and space for experimentation and learning to overcome disappointing crop performance. Together, this hampered Jatropha’s potential to challenge the energy, agricultural and rural development regimes. Nevertheless, the Jatropha experience did initiate the development of policy and regulation and stimulated interaction and collaboration between specific groups of stakeholders, which could provide the basis to capture future biofuel momentum in Mozambique.